Combined endoscopic and ursodeoxycholic acid treatment of biliary cast syndrome in a non-transplant patient - Katsinelos, Panagiotis (The WJG Press and Baishideng, 2008)
A 76-year-old diabetic man underwent cholecystectomy for gangrenous calculous cholecystitis. His postoperative course was complicated by the development of Candida albicans esophagitis necessitating antifungal therapy, and total parenteral nutrition (TPN) for 15 d. Seven weeks after cholecystectomy, he presented with cholangitis. Endoscopic retrograde cholangiopancreatography (ERCP) demonstrated extrahepatic filling defects. Despite endoscopic extraction of a biliary cast, cholestasis remained unchanged. Oral administration of ursodeoxycholic acid (UDCA), 750 mg/d, resulted in normalization of liver function tests. We, therefore, propose for the first time, combined endoscopic plus UDCA treatment for the management of biliary cast syndrome.